Struktur Komunitas Makroalga di Perairan Pantai Nusa Dua, Pulau Bali - Puspitayanti, Putu Sri Dewi; Wijayanti, Ni Putu Putri; Dewi, Ayu Putu Wiweka Krisna (Journal of Marine Research and Technology, 2026)
Macroalgae are essential components of coastal ecosystems that play a significant role in maintaining the sustainability and balance of aquatic ecosystems. This study examined the species composition, percentage cover, and community structure of macroalgae in the waters of Nusa Dua Beach, Bali Island. Data collection was carried out in September 2025 at four sampling stations using a 1×1 m quadrat transect method with systematic random sampling. The analysis included percentage cover as well as the calculation of the diversity index (H'), evenness index (E), and dominance index (D). The results showed that 34 macroalgal species were recorded, belonging to the divisions Chlorophyta, Rhodophyta, and Ochrophyta. The division Chlorophyta consisted of 9 genera, the division Rhodophyta consisted of 12 genera, and the division Ochrophyta consisted of 6 genera. The percentage cover of macroalgae ranged from 23.51% to 45.77%, with Gracilaria vermiculophylla identified as the species with the highest percentage cover. The diversity index (H') ranged from 2.61 to 3.25, the evenness index (E) ranged from 0.82 to 0.95, and the dominance index (D) ranged from 0.04 to 0.11, indicating that the macroalgal community structure in the waters of Nusa Dua Beach was relatively stable.